Penerapan Media Realia Untuk Meningkatkan Kecerdasan Naturalis Anak - Ramdani, Zuhud (Universitas Hamzanwadi, 2017)
The study aims to determine the Realia implementation of the use of media promoting child naturalist intelligence. The Method used in this study is a research method of action cosisting of four stages : Planning, implementation, observation, and reflection. Data collection techniques in this research observation , interview, and documentation study. Action research was conducted in May-July 2015, against 22 Children in Group B TK Bumi Gora Selong. These results indicate that the use of realia media can improve childres’s intellegence naturalist. The average naturalist children at the pre-cycle recorded at 40,77%, the score increased to 62,18% at the end of the cycle to-1,and then increased to 85,4% at end of 2end cycle. Results of this study implies that media use realia can be used as an alternative method that is good for improving intellegence naturalist